Caracterización morfológica de hongos fitopatógenos en el cultivo de haba (vicia faba l.) sector La Urbina, cantón Pillaro, Tungurahua 2015 - Soria Guerra, Alex Mauricio (2015)
The present work was developed in the Cotopaxi province, Latacunga canton, located at 2850 mnsm, latitude 0° 55' 44.8" S and longitude 78° 37' 24.2" W with the objective of characterizing morphologically, the phytopathogenic fungus in the (Vicia faba L.) bean crop at the La Urbina sector, Pillaro canton, Tungurahua province. Identifying the phytopathogenic greatest impact in crop production. Its signs and symptoms are characterizing its macro and micro structures and describing its life cycle in laboratory conditions. Through, the inoculation of the fungus used as a PDA (potato dextrose agar) crop medium and then, it is directly looked and microscopically, throughout its lifecycle and are recording all the work in photography, getting results as the crop bean is reported to Botrytis fabae L. such as the phytopathogenic fungus greatest impact on crop production.